Infrastruktur Transportasi dan Kinerja Ekspor dari Tiga Kelompok Komoditas Indonesia - Daniswara, Adrian Pandhito; Ikhsan, Mohamad (UI Scholars Hub, 2022)
This study aims to assess the impact of road and port infrastructure quality of Indonesia and its trade partners, on Indonesia’s export performance in total as well as on three commodity groups, consisting of mineral, base metals, and manufactured products. Using the Gravity Model with panel data from bilateral export value with 18 largest trade partners in 2007 to 2018, this study found that the proxy of transportation infrastructure quality of both countries are significant and positively impact Indonesia’s total export performance. This study also found that better transportation infrastructure quality has stronger impacts on base metals and manufactured products rather than mineral products, considering each characteristics.